Tecnologias e formação de professores de matemática: uma temática em questão - Malaquias, Arianny Grasielly Baião (2018)
This research aims at identifying and analyzing the theme “technology and mathematic teachers education” on the thesis and dissertation publishedby post-graduation programs in Mathematics Education and programs in Sciences Educations and Mathematics all over Brazil. It is part of the study subject entitled Theories of Education and Pedagogical Processes in the Post-Graduation Program in Education at Pontifical Catholic University. In order to deal with this object, we chose the methodology of research called State of Knowledge so that we were able to identify the genesis that constituted the studied theme itself (SAVIANI, 2007; ROMANOVISKI; ENS, 2006; MORAES, 2016). The corpus was organized by selecting the data taken from Brazilian libraries integrated to the universities which held Post-Graduation Programs in Mathematics Education and programs in Sciences Educations and Mathematics, in the Thesis Bank of Capes, in the Digital Library of Theses and Dissertations (BDTD) and in the survey organized by Fiorentini, Passos and Lima (2016). At the end, the research carried out resulted in 44 theses and dissertations that are part of the corpus of the knowledge state, we identified that the first production of this nature was a Master's dissertation defended in the country in 1999. Therefore, the investigative study that will be carried out will have as an initial timeframe for the year 1999 and will reach the year 2015, since it is the year that starts this research. The accomplishment of a file that identified author, title, year of defense of the thesis, guideline, institution, keywords, studied subject, most cited technological artifacts, terms used to deal with technologies, teacher training conception, vision about the use of technologies for the formation of the teacher of Mathematics and authors of the bibliographical references of each thesis revealed less apparent data of the subject studied. In the effort to capture the real movement of the relation between technologies and the formation of teachers of Mathematics, we have proposed the exercise, based on the philosophical presuppositions of historical and dialectical materialism, to think about this relation in its contradictions and historicity. The analysis was carried out taking as a particularity in this relation the discourses that guide the academic production on the theme "technologies and training of Mathematics teachers". Regarding the relationship between technologies and education, we take as reference the following authors: Vieira Pinto (2005a, 2005b) and Peixoto (2015, 2016). For the historical-critical and dialectical analysis of the data, we are especially based on Duarte (1998, 2006, 2010a, 2010b, 2013), Saviani (2007, 2013), Lefebvre (1975), Kosik (1976), Martins (2006). For the analysis of the conceptions of teacher training in mathematics for the use of technologies, we take as reference: Echalar, Peixoto and Carvalho (2015), Duarte (2000, 2011, 2013) and Vieira Pinto (2005a; 2005b). The results reveal that the treatment of the relations between technologies and education in the academic production on technologies in the formation of teachers of Mathematics oscillates between an instrumental and deterministic tendency (PEIXOTO, 2015). We observe that the training of teachers of mathematics for the use of technologies is discussed from the perspective of the epistemology of practice indicating that the necessary articulation between theory and practice has valued practical knowledge rather than theoretical. We also perceive that the teaching methodologies that derive from the discourses that guide the academic production on the studied subject have as a dominant tone the changes that must occur in the teacher's practice in face of the transformations that need to happen in the school with the insertion of the technologies.